The importance of perceived social support for symptoms of depression and academic stress among university students– A latent profile analysis - Martyna Kotyśko; Joanna Frankowiak (PLoS ONE, 2025)
The aim of the study was to identify, among university students, profiles featuring severity of depressive symptoms, academic stress, and perceived social support and to compare the profiles by gender and current use of professional support. An online cross-sectional study of 1,519 college students in Poland was conducted between March and April 2021. Depressive symptoms were measured using the Center for Epidemiologic Studies Depression Scale—Revised (CESD-R), perceived social support was gauged with the Multidimensional Scale of Perceived Social Support (MSPSS), and academic stress was determined using a short scale of the author’s own design. The main analysis used in the study was latent profile analysis (LPA), which represents a person-centered approach. It allows researchers to identify the structure of the research sample due to the presence or severity of the variables included in the analysis. Four profiles emerged from the analysis: (1) low intensity of depressive symptoms and academic stress with social support (53%); (2) average intensity of depressive symptoms and academic stress with reduced social support from a significant other (19%); (3) high intensity of depressive symptoms and academic stress with low perceived social support (10%); and (4) high intensity of depressive symptoms and academic stress with support from a significant person (18%). Gender and current use of support were factors that significantly differentiated the profiles. Capturing the diversity of the subjects in terms of the severity of depressive symptoms and academic stress in the context of perceived social support provides an opportunity to gain a better understanding of their situation and, consequently, to take more appropriate measures to improve their situation.